Photoinduced Synthesis of Hierarchical Flower-Like Ag/Bi2WO6 Microspheres as an Efficient Visible Light Photocatalyst - Shuisheng Wu; Nianyuan Tan; Donghui Lan; Bing Yi (International Journal of Photoenergy)
A series of three-dimensional microflower-like Ag/Bi2WO6 composites were synthesized through a simple and practical photoreduction process with different photoreduction times. The UV-visible diffuse reflectance spectra indicate that the spectrum of Ag/Bi2WO6 is significantly red-shifted compared to pure Bi2WO6 microspheres in the visible light region. The photocatalytic activities of the as-prepared samples were evaluated by the decolorization of rhodamine B under visible light irradiation. The photocatalytic reaction rate constants of the Ag/Bi2WO6 with a photoreduction time of 20 min was 3.60 times bigger than those of pure Bi2WO6. The enhanced photocatalytic activity could be attributed to the synergistic effect of increased light absorption range and the effective separation of photogenerated carriers caused by Ag nanoparticles.